The Comparison of Education System in The World - Waliyul Maulana Siregar (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
Each country has a different educational system with an emphasis on certain variables in education. In the variable contained goals that will be achieved both long and short term. So that will provide direction for the country to create the human and the shape of the State they want based on the human resources they plan based on the education system. The author tries to compare the three countries of Indonesia, Malaysia, and Finland with the hope that eventually the author will know what things to consider when determining an education system. This is in line with Kendall and Nicholas Hanc's suggestion that the purpose of comparative education is to know what principles actually underlie the regulatory development of the national education system. The progress of a State is certainly accompanied by progress in education. The better of education quality of course it makes the better of quality of human resources that produces. Otherwise, if only the low quality of education Human Resources produced is also low. Once the importance of educational role in advancing a State, it takes a variety of ways to advance education. For a nation that wants to move forward, education must be seen as inseparable from the role of progress of a nation. Of course a nation's education has different educational conditions, both within the scope of history, education system and policy. Three countries namely Indonesia, Malaysia, and Finland as a country that always follow the development of education issues in advancing a nation. In line with that, of course, each country has similarities and differences in education model in developing the quality of education is getting better.